The Fernando Coronil reader : the struggle for life is the matter - Coronil, Fernando, 1944-2011 (Duke University Press, 2019)
In The Fernando Coronil Reader Venezuelan anthropologist Fernando Coronil challenges us to rethink our approaches to key contemporary epistemological, political, and ethical questions. Consisting of work written between 1991 and 2011, this posthumously published collection includes Coronil's landmark essays Beyond Occidentalism and The Future in Question as well as two chapters from his unfinished book manuscript, Crude Matters. Taken together, the essays highlight his deep concern with the Global South, Latin American state formation, theories of nature, empire, and postcolonialism, and anthrohistory as an intellectual and ethical approach. Presenting a cross section of Coronil's oeuvre, this volume cements his legacy as one of the most innovative critical social thinkers of his generation.